2021
DOI: 10.1002/isd2.12185
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption of BYOD in South African small and medium enterprises

Abstract: The advancement in technological development is now altering the conventional order in the diffusion of Information Technology innovation from a top‐down approach (organization to employees) to a bottom‐up approach (employees to organization). This change is more notable in developed economies and has led to the bring your own device (BYOD) phenomenon, which promises increased productivity for employees and their organizations. There have been several studies on the corporate adoption of BYOD, but few have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…These factors vary depending on the level of development of a country. This makes it difficult to generalize factors that influence firms’ innovation in developed countries over developing countries (Akin‐Adetoro & Kabanda, 2021; Sun & Mamman, 2021). Thus, it is critical to understand the factors that drive innovation of SMEs (Abdu & Jibir, 2018).…”
Section: Literature Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…These factors vary depending on the level of development of a country. This makes it difficult to generalize factors that influence firms’ innovation in developed countries over developing countries (Akin‐Adetoro & Kabanda, 2021; Sun & Mamman, 2021). Thus, it is critical to understand the factors that drive innovation of SMEs (Abdu & Jibir, 2018).…”
Section: Literature Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
“…Akin‐Adetoro and Kabanda (2021) conducted a study in South Africa to investigate factors influencing the adoption of innovation by SMEs. The study found that the resources of an organization have a positive influence on its innovation.…”
Section: Literature Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations